2021
DOI: 10.1111/jade.12379
|View full text |Cite
|
Sign up to set email alerts
|

‘Stream and Learn’: An Experiment to Reconnect Design Students with Theoretical Contents during the Pandemic

Abstract: As most GenZ and Millenial students now study at home, young people have shifted their media content consumption, with streaming platforms being among GenZ and Millenials favorites since the first lockdown. Could ‘Netflix and chill’ be turned into a creative learning activity for design students? As theoretical online learning is often associated with unliteral conference calls with no participation from students, we propose an experiment where joining an activity related to relaxation or even procrastination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nevertheless, previous studies showed converting the design studio is not a simple copy-paste task; there are several failed examples, and conversion requires the collaboration of all parties and rigorous hard work over several years [4]. Furthermore, in other design disciplines (e.g., fashion) researchers revealed good results for ODD methods in research/theory modules during the pandemic [18,33]. Online Design and Delivery comes with its shortcomings: Miller and Lu [10] point out the need for intentional and well-informed change in order to respect and protect intellectual knowledge, integrity and knowledge capacity and the management of HE while embedding ODD into F2F.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, previous studies showed converting the design studio is not a simple copy-paste task; there are several failed examples, and conversion requires the collaboration of all parties and rigorous hard work over several years [4]. Furthermore, in other design disciplines (e.g., fashion) researchers revealed good results for ODD methods in research/theory modules during the pandemic [18,33]. Online Design and Delivery comes with its shortcomings: Miller and Lu [10] point out the need for intentional and well-informed change in order to respect and protect intellectual knowledge, integrity and knowledge capacity and the management of HE while embedding ODD into F2F.…”
Section: Discussionmentioning
confidence: 99%
“…The BOL and BL methods in online research/theory modules have not been investigated as much as design studio modules in design education. Urban design [18] and fashion [33] disciplines reported positive changes in their T and L for research/theory modules with ODD. Peimani and Kamalipour [18] analysed their delivery before and after migration to online platforms due to the pandemic and the effects of BOL on T and L and concluded that challenging a fixed pedagogical framework is important for HE.…”
Section: Online Design and Delivery In Research/theory Modulesmentioning
confidence: 99%
See 1 more Smart Citation